Analysis of the Zoning System from the Perspective of Education Decentralization at the Department of Education and Culture - Februati Trimurni; Wiro Oktavius Ginting; Krislin Margarettha Hasianna Sitorus (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The purpose of this study is to examine the secondary school zoning system policy in the New Learner Acceptance (PPDB) from a decentralization standpoint. The zoning system policy can help achieve sustainable development that takes the community's socioeconomic circumstances into account. This study uses the Lindblom incremental model and includes the following analysis indicators: participation of actors and stakeholders, ongoing renewal, and adaptation to community conditions and requirements. This paper uses a descriptive qualitative method, collecting data through in-depth interview techniques, observation, and documentation. Research informants were selected from various parties, namely the Education and Culture Office of Medan City, the Medan City Government, the Regional People's Representative Council (DPRD), Non-Governmental Organizations (NGOs), and affected communities. The results showed that the Education and Culture Office of Medan City uses Google Maps to determine the distance between possible new students' homes and the targeted schools as a zoning determination tool. Based on previous years, regulations pertaining to the proportion of new student admissions from school capacity are also renewed. The DPRD, the Medan City Education and Culture Office, NGOs, the community, and public schools that oversee the zoning system are some of the other participants and stakeholders in the policy. This study recommends paying more attention to students who live in zoning-unserved areas, perhaps by constructing public schools in these areas more rapidly.